MRI/MRS Study of ADEM - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2004)
Magnetic resonance imaging and H magnetic resonance spectroscopy were used to detect possible structural and neurochemical abnormalities in two children, ages 6-months and 4.5 years, with acute disseminated encephalomyelitis at the State University of New York, Stony Brook, New York.